ANTIDIABETIC ACTIVITY OF ENDOPHYTIC FUNGI ISOLATED FROM FICUS RELIGIOSA - Tiwari, Palak; R, Nathiya; Mahalingam, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective- The aim was to study in vitro anti diabetic activity of endophytic fungi isolated from Ficus Religiosa. Method- The explants (leaves and stem) were processed on the potato dextrose media nine colonies was found and colony frequency was calculated. All the colonies were transferred onto potato dextrose broth and incubated for 21 days. The crude was extracted using three solvents petroleum ether (0.1), diethyl ether (2.8) and ethyl acetate (4.4). Three assays were performed to determine in vitro anti diabetic activity of crude extract (Î±-amylase inhibition assay, Î±-glucosidase inhibition assay and glucose diffusion assay) and the % of inhibition by crude and standard acarbose was calculated with standard error mean. Results- The endophytic fungi shows the highest % of inhibition for Î±-amylase inhibition assay (91 % Â± 0.06), Î±-glucosidase inhibition assay (42% Â± 0.01). Conclusion-The results indicates that the hypoglycemic activity of the endophytic crude extract has been proved, hence further studies are focused on to isolate and purify the bioactive compounds and test for in vivo animal studies to confirm the anti diabetic activity. Keywords: Endophytic fungi, Antidiabetic activity, Î±-amylase, Î±-glucosidase.